MetricsCloud: Scaling-Up Metrics Dissemination in Large Organizations. (10th December 2014) - Staron, Miroslaw; Meding, Wilhelm
Abstract : The evolving software development practices in modern software development companies often bring in more empowerment to software development teams. The empowered teams change the way in which software products and projects are measured and how the measures are communicated. In this paper we address the problem of dissemination of measurement information by designing a measurement infrastructure in a cloud environment. The described cloud system (MetricsCloud) utilizes file-sharing as the underlying mechanism to disseminate the measurement information at the company. Based on the types of measurement systems identified in this paper MetricsCloud realizes a set of synchronization strategies to fulfill the needs specific for these types. The results from migrating traditional, web-based, folder-sharing distribution of measurement systems to the cloud show that this type of measurement dissemination is flexible, reliable, and easy to use.